Evaluation and management of systemic corticosteroids-induced ocular hypertension in children with non-Hodgkin lymphoma - Yitian Chang; Yitian Chang; YuTong Zhang; Zhihua Cui; Xianmei Jin; Yufei Zhao; Lingling Liang; Jian Chang (Frontiers Media S.A., 2022)
PurposeTo investigate the effect of systemic corticosteroids (CSs) on ocular hypertension (OHT) and to evaluate the management of OHT in children with non-Hodgkin lymphoma (NHL).MethodsMedical records of children with NHL treated in our institution between October 2016 and October 2019 were reviewed. The enrolled patients were divided into the mature B-cell lymphoma (MBL) group and lymphoblastic lymphoma (LBL) group based on pathology. Data on routine ophthalmic examinations and management of OHT were recorded.ResultsOf the 54 recruited patients, 38 patients (70.4%) had LBL, and 16 (29.6%) had MBL. Thirty-one patients (57.4%) developed OHT, 24 patients (77.4%) in the LBL group, and 7 (22.6%) in the MBL group. Twelve patients (38.7%) were identified as high responders (10 with LBL and 2 with MBL). Symptomatic patients had a higher mean peak IOP than asymptomatic patients (p=0.006). A total of 74.2% of OHT was controlled with antiglaucoma medications (100% in the MBL group vs. 66.7% in the LBL group, significant variation, p < 0.001). In total, 8 patients (25.8%) underwent tapering of the CSs dose. The duration of OHT was shorter in the MBL group than in the LBL group (p = 0.003). No patients were found to have glaucomatous damage or cataracts.ConclusionsPatients receiving systemic CSs had a higher risk of developing OHT, but the pattern of CSs administration might be a critical factor in the risk and severity of OHT. Tapering of CSs dose should be considered the first line for the management of OHT during high-dose CSs therapy.